Curcumin from turmeric (Curcuma longa) induced apoptosis in human mammary carcinoma cells (MDA-MB-231) - Saiful Yazan, Latifah; Ahmad, Faujan; Lee, Pei Sze; Abdul Rahim, Raha; Abdul Hamid, Hisyam; Ooi, Choong Li (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2006)
Introduction: Curcumin, a natural compound present in turmeric (Curcuma longa) has been known to possess both anti-inflammatory and antioxidant effects. Objectives: The objectives of the study were to evaluate the cytotoxic activities and to determine the mode of cell death induced by curcumin towards the human mammary carcinoma cells (MDAMB-231). Methodology: Cytotoxicity of curcumin and its effect on cell viability were determined by using MTT assay and trypan blue dye exclusion method, respectively. The mode of cell death was detected by viewing under a light microscope and through DNA fragmentation analysis. Results and discussion: Curcumin was cytotoxic to MDA-MB-231 cells with the IC50 of 17.25 ì g/ml. Cell viability treatment using curcumin at concentrations of 30 ì g/ml and 10 ì g/ml was significantly (p<0.05) reduced at 48 and 56 hours, respectively, compared to the control. Cells treated with curcumin (30, 10, 3, and 1ì g/ml) showed apoptotic features such as shrinkage of cell, membrane blebbing, chromatin condensation and nuclear fragmentation under a light microscope. DNA extracted from cells treated with curcumin at all concentrations were intact after 24 hours but fragmented after 72 hours, forming DNA laddering on agarose gel, a hallmark of apoptosis. Conclusion: Induction of apoptosis in breast cancer cells by curcumin suggests its potential use as a strategy for cancer control.